Comparison of Early Outcomes for Normothermic and Hypothermic Cardiopulmonary Bypass in Children Undergoing Congenital Heart Surgery - Corno, Antonio F.; Bostock, Claire; Chiles, Simon D.; Wright, Joanna; Tala, Maria-Teresa Jn; Mimic, Branko; Cvetkovic, Mirjana (Frontiers in Pediatrics, 2018)
Objective Early outcomes comparison of normothermic (>35oC) cardiopulmonary bypass (N-CPB) with conventional hypothermia (H-CPB). Methods Data from 99 patients operated with N-CPB(n=48) or H-CPB(n=51) were retrospective reviewed: aortic X-clamping and CPB duration, vasoactive inotropic score (VIS), arterial lactate, pH and base excess, urine output, extubation, PICU stay, transfusion requirements, chest drain losses, costs of transfusions. Results The two groups were homogeneous for diagnosis, surgery and demographic variables: N-CPB age 7.76.1months(4days-23.0months), weight 6.22.4kg(2.8-12.0kg), and H-CPB age 6.66.5months(1day-23.6months), weight 6.12.4kg (2.5-12.0kg). Aortic X-clamping was shorter in N-CPB vs H-CPB:58±37’(0-131’) vs 76±37’(0-142’,P=0.01) as CPB:94±41’(33-197’) vs 116±41’(50-208’,P=0.005). There were no hospital deaths in either group. VIS in N-CPB was lower than H-CPB on PICU arrival (9.7±5.9vs13.4±7.9,P<0.005), after 4 hours (7.0±5.2vs11.1±7.3,P<0.001) and 24 hours (2.8±3.6vs5.6±5.6,P<0.003); arterial pH was better at PICU arrival (7.33±0.09vs7.30±0.09,P=0.046) and after 24 hours (7.37±0.05vs7.35±0.05,P=0.01). Extubation was in N-CPB earlier than in H-CPB (22±27vs48±57hours,P=0.003) as was PICU discharge (61±46hoursvs87±69hours,P=0.021). Transfusions in operating room were lower with N-CPB vs H-CPB for RBC(P=0.007), FFP(P=0.033), cryoprecipitate(P=0.031), and platelets(P=0.018); transfusion of cryoprecipitate and platelets during first 24 hours were lower for N-CPB vs H-CPB (P=0.046 and P=0.029 respectively). In PICU there was reduced requirement in N-CBP vs H-CPB for FFP(P=0.046) for cryoprecipitate(P=0.018) and platelets(P=0.024), while no difference in transfusions of RBC(P=0.495) and FFP(P=0.202) Total amount of transfusions was lower for N-CBP:157±114mL(0-450mL) vs H-CPB:232±150mL(0-590mL)(P=0.004) as amount in mL/kg:27±21mL/kg(0-89mL/kg) vs H-CPB:47±39mL/kg(0-164mL/kg) (P=0.001). Chest drain losses on PICU arrival, after 4 and 24 hours were lower with N-CPB vs H-CPB (P=0.013, P=0.025 and P=0.043 respectively). Reoperation for bleeding was not different: 0/48(=0%) in N-CPB vs 2//51(=3.9%) in H-CPB (P=0.08). In N-CPB 3/48(=6.3%) patients require no transfusion vs 2/51(=3.9%) in H-CPB (P=0.30). Tranexamic acid infusion was requested in 7/48(14.6%) patients with N-CPB vs 18/51(=35.3%) in H-CPB (P=0.009). Total costs/patient of trnasfusions (RBC,FFP,cryoprecipitate,platelets) were lower in N-CPB vs H-CPB for first 24 hours:204±169£(0-545£) vs 306±254£(0-892£) (P=0.011) as in total PICU stay:239±193£(0-625£) vs 427±337£ (0-1074£) (P=0.001). Conclusions N-CPB reduces inotropic and respiratory support, shortens PICU stay, and decreases peri-operative transfusion requirements, with subsequent costs reduction, compared with conventional H-CPB. Wider use of N-CPB in pediatric cardiac surgery should be taken into consideration.